Analysis of Student Participation in University Organization Using Partial Least Square-Structural Equation Modelling - Muhammad Zuhal Lukman (Syntax Corporation Indonesia, 2022)
This study aims to find the effect of organizational climate and motivation on member participation in student organization activities. The sample in this study amounted to 113 members of the Hasanuddin University Political Science Student Association. Data were collected through questionnaires and then analyzed using the partial least squares structural equation modeling technique available in the SmartPLS program. The results of this study indicate that organizational climate and motivation have a positive and significant influence on member participation in organizational activities. The implication of the statement shows that maximizing the level of participation, it can be done by strengthening and adjusting the dimensions of values contained in the organizational climate and motivational constructs.